Leadership Coaching in Public Organizations: (Meta-Analysis of Articles Published on Scopus from 2011 until 2024) - Rahmayanti (JURNAL SIGNAL, 2023)
Research on leadership coaching in public organizations is an important role in achieving government goals. This research aims to analyze previous articles as a reference for leaders in managing human resources, especially in public organizations. This research uses a quantitative method in the form of a meta-analysis study that takes the main data from Scopus with a time span from 2011 to 2024. The results of the research show that there are 15 articles found, with the finding that 2022 is the highest year compared to other years. A total of 8 articles from the field of social sciences were published in Scopus and 1 article in the health field occupied the smallest position in the research period this analysis was carried out. The United States is the highest country that wrote as many as 5 articles compared to other countries, and no articles have been found from Indonesia researchers so the research conducted this time has positive implications for opening up opportunities for researchers from Indonesia and other countries to research on mentoring leaders in public organizations.